Quiescent center initiation in the Arabidopsislateral root primordia is dependent on the SCARECROW transcription factor - Goh, Tatsuaki; Toyokura, Koichi; Wells, Darren M.; Swarup, Kamal; Yamamoto, Mayuko; Mimura, Tetsuro; Weijers, Dolf; Fukaki, Hidehiro; Laplaze, Laurent; Bennett, Malcolm J.; Guyomarc'h, Soazig (Company of Biologists, 2016)
Lateral root (LR) formation is an important determinant of root system architecture. In Arabidopsis, LRs originate from pericycle cells, which undergo a programme of morphogenesis to generate a new LR meristem. Despite its importance for root meristem organisation, the onset of organizing center (termed quiescent center; QC) formation during LR morphogenesis remains unclear. Here, we used live 3D confocal imaging to monitor cell organization and identity acquisition during LR development. Our dynamic observations revealed an early morphogenesis phase and a late meristem formation phase as proposed in the bi-phasic growth model described by Sussex and co-workers. LR QC establishment coincided with this developmental phase transition. QC precursor cells originated from the outer layer of stage II LR primordia, within which the SCARECROW (SCR) transcription factor was specifically expressed. Disrupting SCR function abolished periclinal divisions in this LR primordia cell layer and perturbed the formation of QC precursor cells. We conclude that de novo QC establishment in LR primordia operates via SCR-mediated formative cell division and coincides with the developmental phase transition.